2019
DOI: 10.1021/acssuschemeng.9b02511
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyst-Free Regioselective C–H Thiocyanation of 4-Anilinocoumarins under Visible Light

Abstract: In the present study, we describe the successful development of a novel and efficient C­(sp2)–H thiocyanation reaction of electron-rich heteroarenes and arenes with readily available ammonium thiocyanate under visible light exposure. Most importantly, the reaction proceeded smoothly without addition of any photocatalyst or strong oxidant, ultimately minimizing the production of chemical waste. The advantages of this reaction met the requirements of green and sustainable synthetic chemistry and may be widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 70 publications
(77 reference statements)
0
30
0
Order By: Relevance
“…Taking into account that the fact coumarin derivatives are very significant motifs in various pharmacological and biological activities and the importance of thiocyanation reaction, in 2019, visible-light was employed for the synthesis of SCN-containing coumarin compounds using NH 4 SCN as thiocyanate source (Scheme ). Although initial experiments for a model reaction were successfully carried out in the presence of various organic photocatalysts, such as rose bengal, acridine red, eosin Y, methylene blue, and rhodamine B, the photocatalyst-free condition gave the corresponding product in higher yield. It was found that the addition of TFA (2 equiv) could increase the yield, and using green LED lamp resulted in a significantly lower yield than blue LED.…”
Section: Multiple Bond Formationmentioning
confidence: 99%
“…Taking into account that the fact coumarin derivatives are very significant motifs in various pharmacological and biological activities and the importance of thiocyanation reaction, in 2019, visible-light was employed for the synthesis of SCN-containing coumarin compounds using NH 4 SCN as thiocyanate source (Scheme ). Although initial experiments for a model reaction were successfully carried out in the presence of various organic photocatalysts, such as rose bengal, acridine red, eosin Y, methylene blue, and rhodamine B, the photocatalyst-free condition gave the corresponding product in higher yield. It was found that the addition of TFA (2 equiv) could increase the yield, and using green LED lamp resulted in a significantly lower yield than blue LED.…”
Section: Multiple Bond Formationmentioning
confidence: 99%
“…22 From this study, the nature of the active oxygen, such as singlet oxygen, oxygen radicals, and hydrogen peroxide, cannot be determined. 23,24 Hence, the ethanol oxidation in the liquid-phase involves two consecutive steps, shown in Scheme 1: (1) the oxidative dehydrogenation of ethanol to acetaldehyde on the catalytic surface (reaction (1)) and (2) the non-catalytic, likely radicalinvolved, autoxidation of acetaldehyde to acetic acid in the liquid phase (reaction (2)). A catalytic pathway of acetaldehyde oxidation is possible depending on the catalyst and conditions.…”
Section: àmentioning
confidence: 99%
“…Using visible light and the widely available ammonium thiocyanate, Yang et al found a novel photocatalyst-free oxidative C(sp 2 )–H thiocyanation process for electron-rich heteroarenes and arenes 36. 21 According to mechanistic research, singlet oxygen is created when light is irradiated and can be a vital stimulant for the reaction to continue. The most appealing aspect of the reaction is that it allows simple bench-top processes because it only requires simple and widely affordable compounds 37 and does not necessitate the use of a transition metal catalysts, photocatalysts, bases, or strong oxidants.…”
Section: Photochemical-induced Thiocyanation Reactionsmentioning
confidence: 99%